CRISPR/Cas: From Tumor Gene Editing to T Cell-Based Immunotherapy of Cancer - Azangou-Khyavy, Mohammadreza; Ghasemi, Mobina; Khanali, Javad; Boroomand-Saboor, Melika; Jamalkhah, Monire; Soleimani, Masoud; Kiani, Jafar (Frontiers in Immunology, 2020)
The clustered regularly interspaced short palindromic repeats system has demonstrated considerable advantages over other nuclease-based genome editing tools due to its high accuracy, efficiency, and strong specificity. Given that cancer is caused by excessive accumulation of mutations that lead to activation of oncogenes and inactivation of tumor suppressor genes, the CRISPR/Cas9 system is a therapy of choice for tumors genome editing and treatment. In defining its superior use, we have reviewed the novel applications of CRISPR genome editing tool in discovering, sorting, and prioritizing targets for subsequent interventions, and passing different hurdles of cancer treatment such as epigenetic alterations and drug resistance. Moreover, we have reviewed the revolutions precipitated by the CRISPR system in the field of cancer immunotherapy, such as identification of immune system-tumor interplay, production of universal Chimeric Antigen Receptor T cells, and inhibition of immune checkpoint inhibitors. The existing challenges and limitations, as well as the prospects of CRISPR based systems, are also discussed.